A posture and mobility training package for care home staff: results of a cluster randomised controlled feasibility trial (the PATCH trial). (31st March 2020) - Graham, Liz; Ellwood, Alison; Hull, Karen; Fisher, Jill; Cundill, Bonnie; Holland, Michael; Goodwin, Madeline; Clarke, David; Hawkins, Rebecca; Hulme, Claire; Patel, Ismail; Kelly, Charlotte; et al.
Abstract: Background: provision of care for care home residents with complex needs is challenging. Physiotherapy and activity interventions can improve well-being but are often time-limited and resource intensive. A sustainable approach is to enhance the confidence and skills of staff who provide care. This trial assessed the feasibility of undertaking a definitive evaluation of a posture and mobility training programme for care staff. Design and setting: a cluster randomised controlled feasibility trial with embedded process evaluation. Ten care homes in Yorkshire, United Kingdom, were randomised (1:1) to the skilful care training package (SCTP) or usual care (UC). Participants: residents who were not independently mobile. Intervention: SCTP—delivered by physiotherapists to care staff. Objectives and measurements: key objectives informed progression to a definitive trial. Recruitment, retention and intervention uptake were monitored. Data, collected by a blinded researcher, included pain, posture, mobility, hospitalisations and falls. This informed data collection feasibility and participant safety. Results: a total of 348 residents were screened; 146 were registered (71 UC, 75 SCTP). Forty two were lost by 6 months, largely due to deaths. While data collection from proxy informants was good (>95% expected data), attrition meant that data completion rates did not meet target. Data collection from residents was poor due to high levels of dementia. Intervention uptake was variable—staff attendance at all sessions ranged from 12.5 to 65.8%. There were no safety concerns. Conclusion: care home and resident recruitment are feasible, but refinement of data collection approaches and intervention delivery are needed for this trial and care home research more widely.